I Have Had Enough: When and How Customer Mistreatment Leads to Coworker Undermining - Huilian, Zhou; Waqas, Muhammad; Yahya, Farzan; Ahmad Qadri, Usman; Zahid, Fatima (Frontiers in Psychology, 2022)
Service workers are more prone to experience customer mistreatment because of their frequent interactions with them. Hence, it compels them to the level where their performance is compromised. Employees who face customer mistreatment feel ill-treated and develop the desire for revenge. Based on exchange and resource perspective, this study examined the relationship between customer mistreatment and coworker undermining, as well as individual level resource-based moderator (service rule commitment) for this relationship. Analysis of time-lagged, dyadic data (51 supervisors, 241 subordinates) from Chinese service industry confirmed that customer mistreatment significantly predicted coworker undermining. In addition, supporting the resource perspective, employees’ service rule commitment affectively restricts the effect of customer mistreatment on coworker undermining. Finally, this study contributes to the customer mistreatment and coworker undermining literature by highlighting their relationship. This study also shows of importance of service rule commitment in restraining the adverse effects of customer mistreatment.